Laparoscopic versus open pyeloplasty: an experience at a tertiary care centre - M., Sunil Krishna; T. A., Moideen Nafseer; Rajendra, Benakatti (International Surgery Journal, 2018)
Background: Ureteropelvic junction obstruction can lead to symptoms such as hydronephrosis and progressive renal damage. Authors explain present primary experiences about laparoscopic pyeloplasty and open pyeloplasty in the treatment of UPJO. Methods: A bidirectional non-randomized study from March 2012 to April 2015 was conducted at a tertiary care centre in southern India. A Total 37 cases, 18 patients in laparoscopic pyeloplasty group and 19 patients in open pyeloplasty group were included. Results: A total of 37 patients were included in the study. 18 patients underwent laparoscopic Anderson-Hyne's pyeloplasty, 19 patients underwent open Anderson-Hyne's pyeloplasty patients. Outcomes were measured in terms of pain, surgery duration, postoperative pain, complications which were significant. Conclusions: Laparoscopic pyeloplasty was found to be better in terms of postoperative pain, hospital stay and complications.